Urban Housing Policies And Standards Of Decent Living - Al Ani, Mohammed Qasim Abdul Ghafoor (Journal of Architecture and environment of child, 2021)
Housing policies are linked to urban development plans for each country, which seek to provide suitable urban environment for human habitation and livelihood as subject to standards of quality of life. Which seeks to solve housing problems, improve living and social conditions of life and achieve a prosperous level of human life and families, including the childhood. So, the aspects of these plans and policies address to achieve their goals, including housing goals, which cities adopt in organizing their urban systems and developing a holistic future vision, to achieve these visions and ideas into a set of planning principles according to locally and internationally norms and standards, with the aim of preparing them to formulate plans and policies that can be implemented, including urban housing policies that work to raise the standard of the quality of a decent living for the human being and his prosperity, including the national policies for housing in the Arab countries in cooperation with United Nations Human Settlements Program. The research problem arises in the lack of clarity of the endeavors of urban development plans and housing policies in the Arab countries and their reluctance to work far from the goals and standards of decent living adopted in developed countries. The research seeks in its goal to direct urban development plans and housing policies to integrate goals that contribute to achieving the well-being of a decent living for the Arab citizens and achieving a better future for his generations.